Development Maqashid Sharia Performance in Islamic Bank - Muhammad Taufik (Journal of Finance and Islamic Banking, 2020)
Islamic banks differ from conventional banks both in philosophy and practice. Its implication is the measurement of performance with financial measures is inappropriate. Maqashid sharia as an alternative continues to develop, so that existing measurements have shortcomings. This study develops the existing measurement of maqashid sharia. The development was carried out in three stages, namely literacy studies, weighted scores, and semi structured interviews. Interviews were conducted with academics of ushul fiqh, Islamic economics, Islamic accounting and practitioners of Islamic banking. Maqashid Sharia Performance (MSP) as a measurement development compiles operational definitions into legal and social requirements. Legal requirements consist of 11 SSB Report indices, 7 product and activity indices, 4 document confirmation indices, 7 zakat indices, and 7 attestation of accounting indices. The social requirements consist of 11 daruriyat ratios, 4 hajiyat ratios, and 2 tahsiniyyat ratios. This research contributes to finding measurements of maqashid sharia that meet the aspects of form and substance and are comprehensive for all levels of daruriyat, hajiyyat, and tahsiniyyat.    Keywords             : maqashid sharia performance, legal requirement, social requirement, financial measurement, Islamic bank